Using UAS for monitoring the summit of the Arenal Volcano Costa Rica - Godfrey, Ian (2023)
The Arenal summit is seldom studied for several reasons. First, the eruptive activity has stopped since October 2010, second the active summit crater C is difficult to reach due to an intense steep climb through the tropical rainforest, and third, the summit has rapidly fluctuating weather patterns that make trails muddy and complicate field work sites. Still there is still significant international and national interest in the Arenal volcano in Costa Rica and our undertakings show the Arenal as it was in September 2022 when the summit was documented. The main objective of this survey was to document any potential emissions being emitted from the summit crater of Arenal. With both Sniffer4D units which gathered and log ged volcanic emission data on NO2, SO2, O2, VOC’s, CO2, CO, PM 1.0, PM 2.5, PM 10, O3, NO2+O3 from the Sniffer4D and SO2, CO2, H2S, HF, HCI, CO, CxHy/CH4/LEL, H2 from the SnifferV. By tracking these emissions at the active summit crater C valued volcanic emission data can be acquired and used by the Arenal SINAC park rangers, Universidad Nacional and the National Risk Management Group in Costa Rica the CNE. In addition, by conducting a survey with the FLIR One Pro thermal IR cameras we can inspect the summit area for potential thermal anomalies. By obtaining this temperature data more will be known about the level of thermal energy release at crater C, combined with the gas emissions recognized by the Sniffer units, a periodic “snap-shot” was obtained for the Arenal volcano. The final objective will be to document the unstable regions of the crater with a UAS and collect high quality videography and imagery used for creating Digital Surface Models with Nira software. We are also able to lift the Sniffer4D as a payload with the DJI Mavic 3 drone and document the degassing fumaroles identified with the thermal cameras. Three drone surveillance flights collected valued data that will contribute to overall general knowledge of the volcanic structure, vegetation coverage, erosion and areas of potential rock falls and fumarole fields.